SEJARAH PERKEMBANGAN PENDIDIKAN ISLAM MASA AWAL DI MALUKU - Muhammad Syafril Sunusi; Bahaking Rama; Andi Achruh (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
The arrival of Islam in Maluku and North Maluku took place at almost the same time. However, the process of institutionalizing Islam in governmental life has only materialized in the following decades or perhaps hundreds of years. The arrival of Islam in Maluku is part of recording the traces of a new civilization that entered Maluku, at least it can be traced through the records of travelers. But the controversy over the accuracy of the data, the traveler determines in his travel notes in Maluku in the 7th century, while the local Maluku people in the 8th century. Of course also according to the graph in the history of the Maluku region the touch of Islam in Maluku in the 14th century. This confusion will become valuable data in conducting in-depth research on the traces of Islam in Maluku by collecting primary and secondary data within the framework of reconstructing the entry of Islam in Maluku. Apart from that, the dispora spread of Islam in Maluku, the trade medium was the initial contact for the entry of Islam in Maluku. Arab traders, Gujarat Persians who traveled in search of spices in Maluku became the beginning of the entry of Islam in Maluku